answersLogoWhite

0


Best Answer

The given expression can be simplified to: 8x squared +9

User Avatar

Wiki User

โˆ™ 2016-04-08 10:02:53
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

Multiplication chart! :)

12 cards

2x1

2x2

2x3

2x4

โžก๏ธ
See all cards

Math and Arithmetic

20 cards

The length of a rectangular floor is 2 feet more than its width The area of the floor is 168 square feet Kim wants to use a rug in the middle of the room and leave a 2 foot border of the floor visib

The perimeter of a rectangle is 18 feet and the area of the rectangle is 20 square feet what is the width of the rectangle

The sum of two numbers is 19 and their product is 78 What is the larger number

A rectangular garden has a perimeter of 48 cm and an area of 140 sq cm What is the width of this garden

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: What is the answer to 5x squared plus 3x squared plus 9?
Write your answer...
Submit
Related questions

What must be added to 5 x squred plus 6x plus 9 so that the sum is negative x squered plus 3x plus 3?

5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6


5x plus 4 - 3x plus 5 plus 2x - 9?

5x + 4 - 3x + 5 + 2x - 9 = 4x


3x squared -5x plus 1 plus 8x squared - 2x -9?

(5x 2 - 8x + 1) + (2x 2 - 4x - 11)


How do you do 3X squared plus 18 plus 9?

The given expression can be simplified to: 3X squared +27


What is 6 plus 2x equals 5x plus 9?

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1


What is 5x plus 9 equals 3x 15?

if you meant 5x+9=3*15 then, 5x = 36, x = 7.2 if you meant 5x+9=3x+15 then, 2x = 6, x = 3


What is 5x plus 7 equals 3x-9?

The answer is -8.


What does 2x plus 10 equals 9 plus 11-3x equal?

2x+10=9+11-3x2x+10=20-3x5x+10=205x=10x=2


What is the answer to 5x-8 equals 3x plus 10?

x= 9


What is the sum of -3x -7x plus 9 and -5x plus 6x-4?

It is -9x plus 5.


What is 1 plus 2(3x plus 4) plus 5x?

It is equivalent to 11x+9 when simplified


Factor 9x squared minus 6xy plus y squared minus 81?

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)


What is the value of the discriminant of x squared plus 3x plus 9?

-27


If 3x plus 9 equals 5x plus 1. What is the value of x?

x=4


How do you solve '3x plus 9 equals 81-5x'?

The problem '3x+9=81-5' can be solved as follows - 3x+9=81-5x Original Problem 3x=72-5x Subtract 9 from both sides of the equation 8x=72 Add '5x' to both sides of the equation x=9 Divide both sides by 8


5x square minus 18x plus 9?

5x² - 18x + 9 = (5x² - 15x) - (3x - 9) = 5x(x - 3) - 3(x - 3) = (5x - 3)(x - 3).


Y equals 5x plus 18 y equals 2x plus 9?

5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3


What is 10y squared -23y plus 9 factorised?

(5x-9)(2x-1) when factored


What is the answer to 3x plus 9 equals 5x minus 4?

3x + 9 = 5x - 43x +13 = 5x13 = 2x13/2 = xso x = 6.5


How do you factor 5x squared plus 45?

5(x^2 + 9)


What is standard form of 10 - 2 x - y 3x plus 1 A 5x plus 2y -9 B -5x - 2y 9 C -5x plus 2y -9 D 2y 5x - 9?

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals", "squared". There are no equations or inequalities in the question: only expressions and there are no standard forms that are any different from what appears in the question.


5x plus 9 equals -3x-4 solve for x?

172=x


What is 5x plus 7-3x-9?

The given expression can be simplified to: 2x-2


What is 5x-4-3x 9 equivialent to?

if you mean 5x-4-3x=9 then x= 6.5


What is the answer to 4 - 3x equals 2x plus 9?

4 - 3x = 2x + 9 Add 3x to both sides: 4 = 5x + 9 Subtract 9 from both sides: -5 = 5x Divide both sides by 5: x = -1